DAMPAK PARIWISATA TERHADAP MATA PENCAHARIAN MASYARAKAT PESISIR KARANGASEM:PENDEKATAN PRO POOR TOURISM - I Wayan, Suardana; I G A, Susrami Dewi (PIRAMIDA, 2015)
Tourism is one of the development activities with high growth prospects. The concern for poverty in tourist destinations becomes the attention of scholars, tourist components, and tourists. Attempts which were made to eradicate poverty, among others are : to engage and make the community as tourism subjects who participated directly in alleviating poverty. One district in Bali that support and develop tourism is Karangasem regency. The slow pace of the community in participating in tourism, caused by mental attitude of the society who don’t have idea how to get out of the poverty cycle, so the motivation to work productively still low. There is a positive influence on the development of tourism on the economic changes of society, especially livelihood. Tourism provides an opportunity change people’s livelihood that increasingly widespread. The development of the first advanced society has a role in influencing other people to change mental motivation to work better. Utilization of skills as a fisherman is offset by enhancement of opportunities for diving tourists, which can be utilized as a sideline to supplement their income opportunities.
Keywords: Tourism impact; pro poor tourism; and livelihoods.